Clinical Significance of Ankle Systolic Blood Pressure Following Exercise in Assessing Calf Muscle Tissue Ischemia in Peripheral Artery Disease. (July 2013) - Khurana, Aman; Stoner, Julie A.; Whitsett, Thomas L.; Rathbun, Suman; Montgomery, Polly S.; Gardner, Andrew W.
Our primary objective assessed whether a decline in ankle systolic blood pressure (SBP) to less than 50 mm Hg after treadmill exercise is associated with lower extremity ischemia, as measured by calf muscle hemoglobin oxygen saturation (StO2 ). Eighty-four patients with peripheral artery disease (PAD) completed a treadmill test. Ankle SBP <50 mm Hg following exercise was observed in only 49% (group 1), whereas 51% had ankle SBP ≥50 mm Hg (group 2). No group differences were observed for the decline in calf muscle StO2 to a minimum value (group 1: 18 ± 21%, group 2: 20 ± 20%; P = .60) and for the time to reach minimum StO2 (group 1: 224 ± 251 seconds, group 2: 284 ± 283 seconds; P = .30). Requirement of ankle SBP to decrease below 50 mm Hg after exercise has little clinical significance for assessing ischemia in calf muscle of patients with PAD limited by intermittent claudication.